2023
DOI: 10.3389/fphys.2023.1096139
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical activity and cardiorespiratory fitness with vascular health phenotypes in older adults: a cross-sectional study

Abstract: Objective: We investigated the associations between physical activity (PA) and cardiorespiratory fitness (CRF) with vascular health phenotypes in community-dwelling older adults.Methods: This cross-sectional study included 82 participants (66.8 ± 5.2 years; 81% females). Moderate-to-vigorous physical activity (MVPA) was assessed using accelerometers, and CRF was measured using the distance covered in the 6-min walk test (6MWT). The vascular health markers were as follows: i) arterial function measured as aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Parsons et al found an association between increased SB and worse cIMT, while an inverse relationship was found between LPA and MVPA with cIMT, although MVPA did not have a stronger association than LPA 65. Several studies (n=5) found no relationship between cIMT and PA 20 49 73–75. Other studies ( n =4) found a negative association between cIMT and PA and/or a positive association between cIMT and SB, but not after adjusting for confounders 19 21 76 77.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Parsons et al found an association between increased SB and worse cIMT, while an inverse relationship was found between LPA and MVPA with cIMT, although MVPA did not have a stronger association than LPA 65. Several studies (n=5) found no relationship between cIMT and PA 20 49 73–75. Other studies ( n =4) found a negative association between cIMT and PA and/or a positive association between cIMT and SB, but not after adjusting for confounders 19 21 76 77.…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, Gando et al suggested no relationship between arterial stiffness with VPA, while there was an inverse relationship for MPA and LPA in older subjects 43. Several studies found no relationship between higher intensity PA with arterial stiffness 23 44–49. Some studies investigated specific patient populations, with differing results for subsets of patients 50 51.…”
Section: Resultsmentioning
confidence: 98%